Land Cover Based on Geophysical Characteristics in the Mount Sirimau Protection Forest Group, Ambon City, Maluku Province - Evelin Parera; Ris H Purwanto; Dwiko B Permadi; Sumardi Sumardi (JURNAL BUDIDAYA PERTANIAN, 2022)
The protected forest as life support ideally has a good performance in this case its vegetation, so that its main function can run well. However, as a forest with various functions, the protected forest of Ambon City, especially the Mount Sirimau Protection Forest Group as a strategic protected forest is located upstream of Ambon City which is very influential on the activities of Ambon City as its downstream, because it has a social and economic impact. The performance of a forest area can be seen from its land cover. In addition, the geophysical characteristics of an area will also affect the land cover of the area. Therefore, the purpose of this study was to determine the condition of land cover in the Mount Sirimau Protection Forest Group based on its geophysical characteristics. The research method used was the survey method and the data analysis method was descriptive analysis. The land covers in the Mount Sirimau Protection Forest Group consisted of seven land covers, spreading over soil types, rock types, topography, and slopes. Intensive management of protected forests is needed according to their geophysical characteristics so that the function of protected forests can be more optimal.